2008
DOI: 10.1038/mt.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

Gene-eluting Stents: Adenovirus-mediated Delivery of eNOS to the Blood Vessel Wall Accelerates Re-endothelialization and Inhibits Restenosis

Abstract: Drug-eluting stents for coronary artery disease results in inhibition of smooth muscle cell (SMC) and endothelial cells which may increase the risk of stent thrombosis. In this study, we attempted to enhance re-endothelialization of deployed stents while simultaneously inhibiting intimal hyperplasia by overexpression of endothelial nitric oxide synthase (eNOS) delivery in the vasculature using an adenovirus gene-eluting stent. Re-endothelialization was significantly greater in vessels obtained from normocholes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 28 publications
1
101
2
Order By: Relevance
“…We have shown that adenoviral delivery of eNOS accelerated re-endothelisation and inhibition of SMC proliferation in atheroclerotic rabbits [9,12]. We and others have also shown that eNOS can be delivered to arterial wall vessels by non-viral means using liposomes with efficacy in the form of endothelium regeneration [10,24] and inhibition of restenosis [10].…”
Section: Adenoviral Delivery Of Nos Genes To the Vasculature Have Shomentioning
confidence: 87%
See 2 more Smart Citations
“…We have shown that adenoviral delivery of eNOS accelerated re-endothelisation and inhibition of SMC proliferation in atheroclerotic rabbits [9,12]. We and others have also shown that eNOS can be delivered to arterial wall vessels by non-viral means using liposomes with efficacy in the form of endothelium regeneration [10,24] and inhibition of restenosis [10].…”
Section: Adenoviral Delivery Of Nos Genes To the Vasculature Have Shomentioning
confidence: 87%
“…We and others have shown the efficacy of eNOS derived nitric oxide in inhibiting SMC proliferation [11,21] as well as in preventing in-stent restenosis [9]. During vascular remodelling after injury, eNOS is known to have a dual role of simultaneously stimulating re-endothelisation of the denuded vessel wall, whilst inhibiting the proliferation of SMCs, and hence neointimal re-growth [9,10]. For this reason eNOS is of major therapeutic interest for reasons of promoting vascular repair and prevention of in-stent restenosis after surgical intervention in atherosclerotic patients.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…It is produced by nitric oxide synthase isoforms, and in particular, we have previously utilized endothelial nitric oxide synthase (eNOS) expression in the vasculature to increase NO production. [11][12][13] We have previously reported on successful transduction of rabbit iliac arteries with therapeutic eNOS gene using adenovirus-mediated gene-eluting stents, resulting in enhanced re-endothelialization with a reduction in intimal hyperplasia at 4 weeks post-gene delivery. 12 However, adenoviral-mediated gene delivery to the blood vessel wall has been associated with inflammation, which may impede progress of this potential therapy to the clinics.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] We have previously reported on successful transduction of rabbit iliac arteries with therapeutic eNOS gene using adenovirus-mediated gene-eluting stents, resulting in enhanced re-endothelialization with a reduction in intimal hyperplasia at 4 weeks post-gene delivery. 12 However, adenoviral-mediated gene delivery to the blood vessel wall has been associated with inflammation, which may impede progress of this potential therapy to the clinics. 14 Non-viral and, in particular, liposome-mediated gene delivery represents an interesting alternative to viral gene delivery as they can deliver a large insert size, and are less immunogenic and have fewer bio-safety concerns.…”
Section: Introductionmentioning
confidence: 99%